World Economy Winter 2016 - World economy is gaining traction - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2016)
World economic growth has picked up from the sluggish pace registered at the start of the year. We expect global growth at PPP exchange rates to accelerate to 3.5 and 3.6 percent in 2017 and 2018, respectively, up from 3.1 percent this year. Growth in advanced economies will continue at a slightly faster pace, fueled by expansionary monetary and increasingly also fiscal policies, particularly in the United States. Rising wages will also underpin growth. Despite the recent agreement of oil producers to cut production, we do not assume oil prices to rise sharply as implementation of the agreement is expected to be only partial and the global oil market should remain well supplied for some time to come. Growth in the emerging economies is set to accelerate gradually over the forecast horizon, but persistence of relatively low commodity prices and structural impediments to growth should restrain the growth momentum going forward. – – Die Weltwirtschaft hat die konjunkturelle Talsohle im Verlauf des Jahres 2016 durchschritten. Der Anstieg der Weltproduktion, gerechnet auf Basis von Kaufkraftparitäten, wird sich in den kommenden beiden Jahren auf 3,5 Prozent bzw. 3,6 Prozent erhöhen, nach 3,1 Prozent in diesem Jahr. Damit haben wir unsere Prognose vom September nicht nennenswert verändert. Der Aufschwung in den fortgeschrittenen Volkswirtschaften wird sich in leicht verstärktem Tempo fortsetzen. Anregend wirken die insgesamt weiter expansive Geldpolitik sowie zunehmend - und nicht zuletzt in den Vereinigten Staaten - auch Impulse von der Finanzpolitik sowie eine allmähliche Beschleunigung des Lohnanstiegs. Dem steht allerdings entgegen, dass die Kaufkraft nicht weiter durch sinkende Energiekosten erhöht wird. Einen deutlichen Anstieg des Ölpreises erwarten wir trotz des OPEC-Beschlusses zur Senkung der Fördermengen nicht, da die angekündigten Produktionskürzungen voraussichtlich nicht in vollem Umfang umgesetzt werden und das Angebot am Ölmarkt noch geraume Zeit reichlich bleiben dürfte. Die wirtschaftliche Expansion in den Schwellenländern dürfte sich im Prognosezeitraum allmählich beleben, aber angesichts weiterhin relativ niedriger Rohstoffpreise und vielfach ungelöster struktureller Probleme keine große Dynamik entfalten.
Keywords: 330; advanced economies; emerging economies; global oil market; quotas; OPEC countries; monetary policy; Japan; Russia; ASEAN